Book club : the next chapter [videorecording (DVD)] - Holderman, Bill; Simms, Erin, 1976-; Keaton, Diane; Fonda, Jane, 1937-; Bergen, Candice, 1946-; Steenburgen, Mary; Nelson, Craig T.; Giannini, Giancarlo; Quarshie, Hugh; Riotta, Vincent; Garcia, Andy; Johnson, Don, 1950- (Universal, 2023)
The highly anticipated sequel follows our four best friends as they take their book dub to Italy for the fun girl's trip they never had. When things go off the rails and secrets are revealed, their relaxing vacation turns into a once-in-a-lifetime cross-country adventure.